2021
DOI: 10.1111/jvh.13594
|View full text |Cite
|
Sign up to set email alerts
|

No influence of hepatic steatosis on the 3‐year outcomes of patients with quiescent chronic hepatitis B

Abstract: The influence of hepatic steatosis on the natural history of chronic hepatitis B (CHB) virus is unclear. Therefore, we investigated whether concurrent steatosis in patients with CHB influences the probability of hepatitis B surface antigen (HBsAg) loss, fibrosis progression and hepatocellular carcinoma (HCC) development. This study enrolled treatment‐naïve patients with virologically (HBV DNA <2,000 IU/ml) and biochemically (alanine aminotransferase level <40 IU/L) quiescent CHB who underwent transient elastog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…Conversely, there are studies that do not consider NAFLD to have an effect on spontaneous HBsAg clearance. A Korean study (HBV DNA-negative CHB patients, n = 720) with 3-year follow up found no correlation between HS and spontaneous HBsAg clearance (P = 0.518) [ 32 ].…”
Section: Interaction Between Hbv Infection and Nafldmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, there are studies that do not consider NAFLD to have an effect on spontaneous HBsAg clearance. A Korean study (HBV DNA-negative CHB patients, n = 720) with 3-year follow up found no correlation between HS and spontaneous HBsAg clearance (P = 0.518) [ 32 ].…”
Section: Interaction Between Hbv Infection and Nafldmentioning
confidence: 99%
“…Nevertheless, several studies showed no correlation between steatosis and fibrosis [ 66 , 67 ]. For instance, in a retrospective study in South Korea, treatment-naïve CHB patients with normal ALT and HBV DNA <2000IU/ml were followed up for 3 years and no correlation was found between HS and fibrosis progression (OR = 1.09, 95%CI 0.64–1.85) [ 32 ].…”
Section: Prognosis Of Hbv Infection Combined With Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…While there exists growing evidence that NAFLD may provide some benefit in reducing disease progression in CHB patients, there are some studies that have suggested otherwise. Jin et al [ 25 ] retrospectively analyzed 720 CHB patients in 3 years and found that HS was not significantly associated with HBsAg seroclearance, fibrosis progression, or HCC development. However, their study may be influenced by its retrospective nature with a relatively short follow-up duration.…”
Section: Interaction Of Chb and Nafldmentioning
confidence: 99%
“…[ 70 , 71 ] In addition, several other studies have suggested that HS is not a risk factor for the probability of fibrosis progression or HCC development in CHB patients. [ 13 , 25 , 71 73 ]…”
Section: Progression and Outcomes Of Chb With Nafldmentioning
confidence: 99%